A study of the usage of Malaysian Mandarin versus Standard Mandarin (Putonghua) in the Malaysian commercial sector - Soo Kum Yoke, Carolyn; Bee Hoong, Tay; Ling Ling, Toh (Institut Penyelidikan, Pembangunan Dan Pengkomersilan, 2010)
This study investigates the use of Malaysian Mandarin and Standard Mandarin (Putonghua) in the Malaysian commercial sector. The primary purpose is to ascertain the viability of using Malaysian Mandarin in business transactions with companies in China. The research also discusses the extent to which Malaysian Mandarin aids the flow of business dealings. A total of 150 respondents were randomly selected to participate in a survey and interview. The results demonstrate a preference for the use of Malaysian Mandarin. However, the study also indicates that the use of Standard Mandarin (PTH) should not be neglected, as respondents perceive it as an added advantage to business. The implication is that both Malaysian Mandarin and Standard Mandarin terms should be introduced into the curriculum to facilitate language use for business dealings with Chinese companies.